Theosophical sociability in Cuba: A first approach to the history of the Cuban theosophical movement at its initial stage (1894-1904) - Rivero Aponte, Andres (2020)
This paper is one of the first approaches to the history of the Theosophical Society in Cuba. Firstly, theosophy is defined and secondly, the emergence and development of the international Theosophical Society as well as the conditions that led to its insertion in Cuban spaces are briefly described. It also covers the emergence and development of the first theosophical lodges on the Island. In other words, this is a presentation of a synthetic vision of the Cuban theosophical movement in its first stage which starts in 1894 and ends in 1904.